Cash Waqf Linked Sharia Micro Insurance (CWLSMI) Sebagai Proteksi Dana Darurat Pelaku Usaha Mikro - Faisal, Ryan (ITB AAS INDONESIA Surakarta, 2024)
The scientific work aims to introduce Cash Waqf Linked Sharia Micro Insurance (CWLSMI), an innovative approach to facilitate Sharia micro insurance contributions for micro-business actors using their owned products. Micro-business actors' product portfolios will be cataloged based on global community interests, and the management will be funded through productive waqf assets. Revenue generated from product sales will fund contributions to Sharia micro insurance for micro-business actors, their families, and contribute to government social security programs. CWLSMI serves as a financial planning reference for micro-business actors, fostering benefits for the halal industry. This qualitative research utilizes a narrative approach, incorporating primary data from search results and stakeholder interviews, complemented by secondary data from scientific journals and government reports. The initiation of CWLSMI is proposed as a recommendation to the government for enhancing the welfare of micro-business actors in Indonesia.